Comprehensive Evaluation of Publication and Citation Metrics for Quantifying Scholarly Influence - Ghulam Mustafa; Abid Rauf; Bilal Ahmed; Muhammad Tanvir Afzal; Adnan Akhunzada; Salman Z. Alharthi (IEEE Access, 2023)
Ranking of researchers based on their scientific impact in a scientific community is indeed a very crucial task. However, identifying the researchers ranking helps the scientific community in various decisions such as awarding scholarships, selection for tenure, awarding achievements, giving promotions, etc. In literature numerous parameters have been proposed for the ranking of researchers, such as publication count, citation count, coauthor count, h-index, and its extensions. The current state-of-the-art research delineates that no such universally accepted parameter exists which can identify the most influential researchers. Therefore, it is necessary to determine an optimal parameter that can effectively rank authors. Furthermore, to identify the best parameter, few of the researchers conducted evaluative surveys as reflected in the literature. In these evaluative surveys, the researchers utilized a limited number of indices on the small and imbalanced datasets, followed by fictional cases and scenarios, this has made it challenging to ascertain the relative importance and impact of each parameter in comparison to the others. This research evaluates the h-index and its thirty-two variants, which are based on the number of publications and citation count category used for ranking the authors. We have collected data from 1050 researchers working in the mathematical domain for our experimental purposes. For the benchmark dataset, we have collected the awardees’ data of the last two decades of four different societies belonging to mathematical domain. First and foremost, we have computed the correlations among the obtained values of the indices to assess their similarities and differences to evaluate indices. The result revealed that there is a high degree of correlation observed among h-index and it’s twenty-four different variants. However, some indices showed a weak correlation, signifying that their rankings were highly dissimilar to those of other indices. Secondly, the position of awardees is checked in the top 10, top 50, and top 100 return records based on the ranking list of each index. The outcome of the last step divulges that A index, E index, H core citation, H2 lower index, K index, M index, and woginger index retrieved almost 80% of awardees in top 10% ranked list. Further, the analysis revealed that most of the winners (awards) were in the top tier, belonging to IMS, LMS, and AMS society returned by hg index, g index, k index, etc. indicating a relationship between the stated societies and the indices.